Valorising literature in the age of technology: some personal reflections - Quayum, Mohammad Abdul (2016)
In a controversial essay in The Atlantic in 1967, “The Literature of Exhaustion,” then America’s leading writer and one of the pioneers of Postmodernism, John Barth (1930-), (somewhat ironically and even hypocritically) proffered that the conventional modes of literary representation have been “used up” and their possibilities consumed through over use. The great preponderance of literature, he argued, belonged to the nineteenth century and its merits have become irrelevant to our generation. More recently, in an article in The New York Observer (June 22, 2010), “Where Have All the Mailers Gone?,” Lee Siegel, has affirmed that “fiction has become culturally irrelevant” in the twenty-first century. Do we have to agree with these cynics and dirge singers and believe that literature is dead? Has it become peripheral and extraneous to our present life? Or is literature still as important as it was, say, during the time of Homer, Aeschylus and Sophocles? This paper will investigate these issues and argue that literature is likely to outlive our current obsessions with technology, because of the many positive influences it has on us as human beings. No matter what the nay-sayers might say, so long as literature empowers our imagination, enriches our cultural traditions and provides a stay against the dehumanising effects of money and matter, it is here to stay; as long as it can inculcate the basic human values of fellowship, patience and love, extend the horizons of our minds and bring joy in our hearts, we will continue to honour, cherish and venerate literature as a form of knowledge that is essentially irreplaceable and indispensable.